The Hélène Cixous reader - Sellers, Susan (Routledge, 1994)
This is the first truly representative collection of texts by Helene Cixous. The substantial pieces range broadly across her entire oeuvre, and include essays, works of fiction, lectures and drama. Arranged helpfully in chronological order, the extracts span twenty years of intellectual thought and demonstrate clearly the development of one of the most creative and brilliant minds of the twentieth century. With a foreword by Jacques Derrida, a preface by Cixous herself, and first-class editorial material by Susan Sellers, The Helene Cixous Reader is destined to become a key text of feminist writing.